Mixed integer programming approach for minimizing train delay / Nurul Liyana Abdul Aziz ... [et al.] - Abdul Aziz, Nurul Liyana; Jalil, Nur Faqihah; Md Shamsul, Faridatul Azra; Abbas, Zaliyah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In the high technological world of today, transportation maintains up with the advancement of human existence and culture. Additionally, it has improved economic structure by speeding up the distribution of economic growth. Malaysia is another nation that offers commuter rail services. The only provider of train commuter services in Malaysia is Keretapi Tanah Melayu, which offers services in the Klang Valley, Penang, Perak, and Johor. Railway service that is readily accessible to the general public is perfect for reducing highway traffic, especially in congested areas, and promoting environmentally responsible and sustainable growth. Malaysians prefer taking the train over driving because it saves them money while avoiding traffic and allows them to reach their destination on time. However, because of the technical fault could impair the railway network, the railway firm frequently encounters unforeseen issues, such as sudden changes to the original schedule (Alwadood et al., 2015). This study is related to public scheduling problems and focuses on train scheduling problem. The aim of this study is to estimate the delay time from Padang Besar to Sungai Petani by using mixed integer programming. The train scheduling problem will be modelled as mixed integer programming and the data will be taken from the KTM Berhad website. By using Microsoft Excel, the model was used to estimate the delay time. At the end of this study, a new train schedules was proposed.